Mosquitoes and Bromeliads - Ana Romero-Weaver; L. Philip Lounibos; Eva A. Buckner (EDIS)
Water can collect in the central tanks or axils of bromeliads, and immature stages of mosquitoes sometimes inhabit these small pools. This article provides recommendations for environmentally acceptable ways to control the production of nuisance mosquitoes in bromeliads; suggestions for planting species of bromeliads less likely to favor the production of mosquito-borne disease vectors; and general advice about personal protection against mosquito bites.